Penyuluhan Kewirausahaan & Workshop Perencanaan Bisnis Menggunakan Business Model Canvas (Bmc) Di Smk Negeri 1 Purbolinggo Kabupaten Lampung Timur - Eny Ivan’s; Novia Ambar Sari; Wintari Mandala; Diky Angga Hendrawan (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
Entrepreneurship is an alternative choice for millennials to pursue it as a main source of income. In the academic environment, entrepreneurship is a subject and a general subject given from elementary school to university level. The output of this course is the interest of students to become entrepreneurs. One of the sub-materials of entrepreneurship is the ability to develop business plans. Business planning is a blueprint for entrepreneurs who have or will run. The approach in business planning that is widely used is the Business Model Canvas. The BMC approach is considered very simple, easy, and complete so that it is able to summarize the business plan in a single sheet of dialog boxes consisting of 9 elements. The purpose of this service activity is to provide counseling and workshops with business planning materials using the BMC approach. Counseling is carried out using lecture and workshop methods with an FGD approach. The results of student service activities become aware of what BMC is and can implement business planning using the BMC approach. Entrepreneurship mentoring activities must continue to be carried out for all circles of society, especially the millennial generation in order to improve the national economy and build the welfare of the community it self.